2022
DOI: 10.1177/00494755221074538
|View full text |Cite
|
Sign up to set email alerts
|

An observational study to compare the diagnostic accuracy of rapid antigen test and rapid antibody tests in various periods of enteric fever

Abstract: A cross-sectional observational study was done on 180 fever patients to assess the diagnostic accuracy of rapid serological tests in early detection (<5 days of fever) of S. typhi and S. paratyphi in comparison to blood culture and Widal test Blood culture was positive in 58 (32.22%) cases. The diagnostic accuracy (<5 days of fever) of rapid antigen test, rapid antibody test, and Widal test was 45.56%, 42.22%, and 41.11% (p = 0.675) while sensitivity was 68.97%, 48.28%, and 46.55%, respectively. In concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Typhi/Paratyphi and other Salmonellae continuously. [ 17 ] As in most of the cases, the second sample in the latter part of the fever is not sent to the lab; therefore, this observation holds practical importance. Moreover, we observed that the sensitivity of the Widal test shooted to 79.31% after five days of fever which was consistent with the antibody principle, and the values were in comparability to Rapid antibody test findings, as both these tests are based on antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…Typhi/Paratyphi and other Salmonellae continuously. [ 17 ] As in most of the cases, the second sample in the latter part of the fever is not sent to the lab; therefore, this observation holds practical importance. Moreover, we observed that the sensitivity of the Widal test shooted to 79.31% after five days of fever which was consistent with the antibody principle, and the values were in comparability to Rapid antibody test findings, as both these tests are based on antibody detection.…”
Section: Discussionmentioning
confidence: 99%